APPROXIMATION OF A FINITE BLASCHKE PRODUCT BY INFINITE ONE - Pandeski, Nikola (Matematichki Bilten, 2002)
Let \(b_n(z)\) be a finite Blaschke product in the unit disk in the plane. We find a sequence infinite Blaschke product which converge to \(b_n(z)\) uniformly on the compact subsets of the unit disk.